Pengaruh Pemberian Pupuk Kandang Kotoran Ayam dan Pupuk NPK Mutiara Yaramila terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacg.) pada Pembibitan Pre Nursery - Mohammad Hertos (Anterior Jurnal, 2013)
This study aims: (1) to determine the effect of chicken manure and Yaramila NPK fertilizer on the growth of oil palm seedlings in pre-nursery nurseries and (2) to determine the single factor of chicken manure and Yamila pearl NPK fertilizer on the growth of coconut seedlings palm in pre-nursery nurseries. This experiment used factorial completely randomized design with three factors and three replications. The second factor studied was: Factor I: Giving Chicken Manure (P) which consists of 4 levels, namely: P0 = 0 ton / ha, P1 = 20 ton / ha, P2 = 30 ton / ha, and P3 = 40 ton / ha. Factor II: Fertilizer Giving NPK Mutiara Yaramila (Y) consisting of 4 levels, namely: Y0 = 0 kg / ha, Y1 = 200 kg / ha, Y2 = 300 kg / ha, and Y3 = 400 kg / ha.As for the number of leaf parameters, the interaction between them does not produce real or very real.The parameters of seed height were 4, 8 and 12 MST (17.9 cm, 34.4 cm and 44.3 cm), stem diameter aged 4, 8 and 12 MST (0.57 cm, 0.60 cm and 0.92 cm), parent root length (25.3 cm) and fresh seed weight (16.87 grams) per day. Chicken Manure Fertilizer at a dose of 40 tons / ha and Yaramila Pearl NPK Fertilizer at a dose of 400 kg / ha (P3Y3).